NOMINALIZATION IN ACADEMIC ENGLISH: ITS LINGUISTIC FUNCTIONS AND STYLISTIC SIGNIFICANCE - Nurmaxmatova Firuza Rasulovna, (TADQIQOTLAR, 2026)
Abstract: Nominalization is a key grammatical feature of academic English. It changes verbs and adjectives into nouns, helping writers express complex ideas clearly and formally.  This article looks  at the structure, functions, and stylistic impacts of nominalization  in  academic  writing.  Relying  on  systemic  functional  linguistics, especially the work of M. A. K. Halliday, the study explains how nominalization helps with  abstraction,  information  density,  objectivity,  and  textual  cohesion.  It  also addresses  the  benefits  and  drawbacks  of  too  much  nominalization,  particularly  in student writing. The analysis shows that nominalization is more than just a grammatical change; it is a strong rhetorical tool in academic communication.